The Existence of Environmental Awareness in the Disaster Theology of Muslim Communities on the North Coast of Java - Maharani, Melisa Diah (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2025)
Purpose- This study aims to explore the paradigm shifts in environmental awareness and disaster theology among Muslim communities on the North Coast of Java, particularly focusing on generational differences between Gen X and Gen Z in responding to ecological crises such as floods. Design/methods/approach- This research employs a qualitative method using surveys and in-depth interviews, supported by literature review. The phenomenological approach is used to examine individual experiences and meanings related to disasters. The analysis framework is based on Peter L. Berger and Thomas Luckmann’s theory of the social construction of reality. Findings- The findings reveal that Gen Z tends to perceive disasters through the lens of environmental degradation and socio-political factors, influenced by digital media exposure and global ecological discourse. In contrast, Gen X adheres more to classical theological interpretations, viewing disasters as divine tests or punishments. However, both generations demonstrate ethical responses that are not solely rooted in theological understanding, but also shaped by evolving social values and knowledge. The typology of ethical-theological attitudes includes fatalism/vitalism in both passive and active forms. Research Implications- This research highlights the dynamic interaction between theology, ecology, and social construction in shaping environmental awareness. It underscores the need for strategic environmental education that integrates religious narratives to foster sustainable behavior, especially in disaster-prone communities with strong religious identities.